Motivational Factors that Encourage Vocational College Students to Continue Their Studies to Bachelor’s Level based on Maslow's Hierarchy Theory - Amat, Ali Firdauz; Amiruddin, Mohd Hasril (Research and Innovation in Technical and Vocational Education and Training, 2024)
A research study was conducted to identify the motivational factors that drive vocational college students to pursue undergraduate studies after completing their diploma program, based on Maslow's Hierarchy of Needs Theory. The study examined the correlation between these factors and students' decisions to further their studies. Questionnaires were distributed to final-year vocational college diploma students in welding technology programs across Malaysia, with 173 study samples. Out of these, 130 students who expressed a desire to further their studies were used for analysis. Data analysis was performed using Statistical Package for the Social Sciences version 26.0, which includes descriptive statistics such as mean, standard deviation, and Pearson's correlation inferential statistics. The study found that self-improvement needs were a factor for intrinsic motivation, while physiological needs were a factor for extrinsic motivation. The study also revealed that intrinsic and extrinsic motivation significantly correlated with vocational college students' motivation to further their undergraduate studies.